Frequency-specific hearing results after stapes surgery for Chinese population otosclerosis with different degrees of hearing loss. (3rd May 2020) - Zhang, Kun; Fang, Yanqing; Wang, Bing; Cheng, Xiaoting; Chen, Bing; Shu, Yilai
Abstract: Background: Frequency-specific hearing studies are important for predicting hearing results and the prognosis after stapes surgery, to prepare for the rehabilitation of frequency-specific hearing in patients with otosclerosis. Objectives: To evaluate outcomes of stapes surgery of Chinese otosclerosis patients with different degrees of hearing loss. Methods: We conducted a retrospective analysis of 213 otosclerosis patients who underwent stapes surgery in our hospital. Pre- and post-operative audiometric evaluation using conventional audiometry. Results: The post-op ABG was less than 20 dB in 94.52% of all cases after surgery. There was no statistical significance of the post-op ABG among different groups at all frequencies except extremely severe group ( p  < .05). There was a significant improvement of both AC and BC thresholds in post-op period and the most significant improvement was found in severe group. There were no serious post-op complications and no re-operations during the follow-up period. Conclusion: Stapes surgery is a suitable treatment option for otosclerosis with mild to extremely severe HL. The mild to moderate hearing loss groups had the most significant improvement of AC thresholds in the low frequency region, and the severe to extremely severe groups appeared in the high frequency region.